2003
DOI: 10.1017/s0033291703008237
|View full text |Cite
|
Sign up to set email alerts
|

The Vulnerable Attachment Style Questionnaire (VASQ): an interview-based measure of attachment styles that predict depressive disorder

Abstract: Background. The Vulnerable Attachment Style Questionnaire (VASQ) was developed to provide a brief self-report tool to assess adult attachment style in relation to depression and validated against an existing investigator-based interview (Attachment Style Interview – ASI). This paper describes the development and scoring of the VASQ and its relationship to poor support and major depression.Method. Items for the VASQ reflected behaviours, emotions and attitudes relating to attachment relationship style, drawn di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
109
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(119 citation statements)
references
References 26 publications
5
109
1
4
Order By: Relevance
“…Additional caregivers were defined as day care providers, such as kindergarten teachers and day care parents who were involved in child rearing. Furthermore, maternal attachment style insecurity was assessed with the Vulnerable Attachment Style Questionnaire (VASQ) [33]. The mother-child interaction was coded by two trained and reliable psychologists who were blinded to the mental health status of the mothers using the Emotional Availability Scales (EA Scales) [3].…”
Section: Methodsmentioning
confidence: 99%
“…Additional caregivers were defined as day care providers, such as kindergarten teachers and day care parents who were involved in child rearing. Furthermore, maternal attachment style insecurity was assessed with the Vulnerable Attachment Style Questionnaire (VASQ) [33]. The mother-child interaction was coded by two trained and reliable psychologists who were blinded to the mental health status of the mothers using the Emotional Availability Scales (EA Scales) [3].…”
Section: Methodsmentioning
confidence: 99%
“…The VASQ (Bifulco et al, 2003) is a brief self-report tool, which assesses general adult attachment. It is designed to assess overall attachment vulnerability as well as two dimensions of attachment: a global dimension of attachment insecurity common to all insecure subtypes (representing a deep-rooted mistrust of others and their motives) and a proximity seeking dimension reflecting the strategy individuals use to manage their insecurity (i.e.…”
Section: Vulnerable Attachment Style Questionnaire (Vasq)mentioning
confidence: 99%
“…2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Another distinguishing feature of this study was the use of the VASQ for the assessment of attachment style. We chose to use this self-report tool as it has been shown to perform somewhat better in predicting depression than other self-report measures of attachment (Bifulco et al, 2003), as well as predicting negative psychosocial well-being and mental health in university students (Carr et al, 2013). The study has several other strengths in that self-reported menstrual phase, age, smoking and BMI were all accounted for in the modelling of cortisol reactivity.…”
Section: Insert Table 2 Herementioning
confidence: 99%
See 2 more Smart Citations